Construct validation of leaders’ motivating language in the context of the hotel industries of Bangladesh and Malaysia - Karim, Md Rabiul; Yean, Tan Fee; Patwary, Ataul Karim; Mohamed, Ahmad Edwin; Abdullah, Haim Hilman (EMERALD, 2021)
Purpose – This study aims to validate the motivating language scale developed by Mayfield et al. (1995) in the context of the hotel industries of Bangladesh and Malaysia. Design/methodology/approach – For Study 1, data were collected from employees (lower and midlevel) of three to five-star hotels in Bangladesh. Customer-contact employees working in four- and five-star hotels in Malaysia participated in Study 2. Both studies featured a cross-sectional survey design. Findings – Factor analysis revealed that both samples provided three-factor solutions for the motivating language scale in both countries. Convergent, discriminant and nomological validity were assessed by testing with outcome variables of motivating language. Research limitations/implications – Future studies may use all three versions of the scale (Bengali, Malay and English) to collect data, as all three have been validated. Originality/value – By validating the Bengali and Malay versions of the motivating language scale, this study contributes to the leadership language literature, specifically that related to hotel industries in developing contexts